MODEL PENGEMBANGAN DESTINASI WISATA PANTAI BOTUTONUO KABUPATEN BONE BOLANGO, PROVINSI GORONTALO - Desrika Talib (Tulisan Ilmiah Pariwisata (TULIP), 2018)
Botutonuo beach is one of tourism destinations in Bone Bolango regency, Gorontalo Province. There are several problems of Botutonuobeach such as human resource, internal and external factors of tourism development, and the development strategy of Botutonuo beach. The fundamental problem is the development of this tourism destination which has not been optimal yet. This research is to provide appropriate guidance in terms of development strategy of Botutonuo beach. The development strategy is to improve the quality of human resource, internal and external factors of tourism development, and the development strategy of Botutonuo beach so that this tourism spot can be developed optimally. This research applies qualitative approach (observation, in-depth interview, and library research). It is conducted to investigate the actual condition of Botutonuo beach such as human resource, SWOT analysis to identify the internal and external factors, and to codify the grand strategy of tourism development of Botutonuo beach. Research result shows that there are several problems on Boutonuo beach. They are; the potentials of Botutonuo beach have not been developed optimally in terms of human resource;the internal and external factors still contain weaknesses and threats, and the best grand strategy of development can be the strategy of SO, WO, ST, WT. Based on research result, it is suggested that the fundamental point to be developed is the quality of human resource. Moreover, in terms of internal and external factors, the government should develop the natural tourism of Botutonuo beach by improving the infrastructure, facilities, accommodation, accessibility, and more interesting tourism attraction. Finally, the government should apply WO strategy as the development strategy of Botutonuo beach